Melatonin rhythm disorder is more pronounced in major depressive disorder with non-suicidal self-injury - Xiaojuan Hu; Xiaojuan Hu; Xiaojuan Hu; Xiaojuan Hu; Aiguo Zhang; Aiguo Zhang; Aiguo Zhang; Chao Wang; Chao Wang; Chao Wang; Xulai Zhang; Xulai Zhang; et al. (Frontiers in Neuroscience)
IntroductionDisruptions in melatonin (MT) rhythms have been linked to major depressive disorder (MDD) and may be further associated with non-suicidal self-injury (NSSI). This study investigates whether MDD patients with NSSI exhibit more pronounced MT rhythm disturbances and whether these disruptions correlate with NSSI-related thoughts and the motivation to cease self-injury.MethodsThe study included 100 participants aged 14–24 years, including 30 healthy controls (HC) and 70 inpatients diagnosed with MDD. The MDD group was further divided into those with NSSI (NSSI group, n = 35) and those without NSSI (Non-NSSI group, n = 35). Salivary MT levels were measured at six intervals (12 a.m., 8 a.m., 11 a.m., 1 p.m., 4 p.m., and 10 p.m.) using enzyme-linked immunosorbent assay (ELISA). The Ottawa Self-Injury Inventory (OSI) assessed NSSI perception and motivation in the NSSI group.ResultsMelatonin levels were significantly lower across all six time points in the NSSI group compared to both the Non-NSSI and HC groups (P < 0.05), and MT circadian rhythms were notably absent in the NSSI group. Correlational analysis revealed specific associations between MT levels and NSSI behavior, with MT levels at 1 PM positively correlated with invasive self-harm impulses (r = 0.487, P = 0.003, 95% CI: 0.141 to 0.834) and MT levels at 8 a.m. and 11 a.m. inversely correlated with the desire to stop self-injury (r = −0.427, P = 0.010, 95% CI: −0.774 to −0.081; r = 0.348, P = 0.040, 95% CI: 0.002 to 0.695, respectively).ConclusionLower MT levels and disrupted circadian rhythms are associated with NSSI in MDD patients, highlighting a potential link between circadian dysfunction and self-injurious behaviors. Further research is needed to clarify the underlying mechanisms of this association.